Peningkatan Keterampilan Manajemen Organisasi Untuk Pengusaha Wanita Anggota Asosiasi Guyub Sido Rukun - Martono, S.; Wulansari, Nury Ariani; Ranihusna, Desti (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
The purpose of this service program is to disseminate the results of the author's research as well as to provide management skills training to female entrepreneurs. The method of implementing the program is carried out through structured training, starting from the first stage, brainstorming with women entrepreneurs who are members of the association. The second stage, held training activities for women entrepreneurs to introduce the concept of management functions. In this training there are practical simulation activities to make managerial planning. The third stage is evaluation to reflect the extent to which training has been well understood. With this service activity, it is hoped that it can become a means for female entrepreneurs in improving business management managerial skills. The results obtained were the association of SMEs, Guyub Sido Rukun, who was very active and they were able to carry out self mapping through understanding management theory, analyzing the situation faced and the solutions to be carried forward.